2009
DOI: 10.1002/bio.1124
|View full text |Cite
|
Sign up to set email alerts
|

A steady‐state and time‐resolved fluorescence, circular dichroism study on the binding of myricetin to bovine serum albumin

Abstract: The binding mechanism of myricetin (Myr) to bovine serum albumin was investigated by using steady-state and time-resolved fluorescence and circular dichroism. The results of the steady-state fluorescence quenching experiment indicate that it is a static quenching process (C(Myr)/C(BSA) < or = 3) at low quencher concentration and the binding site is located near the Trp212 residue. The association constants at the different temperatures were calculated. From the thermodynamic parameters, enthalpy change (DeltaH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…3 (Table 1) are 3 orders of magnitude greater than the maximum diffusion collision quenching rate constant (2.0 Â 10 10 L mol À 1 s À 1 ) of a variety of quenchers with biopolymer [15]. Therefore, the fluorescence quenching of Lys by myricetin with or without Cu 2 + or Fe 3 + should be resulting from static quenching mechanism owing to a complex formation rather than a dynamic quenching mechanism at low concentrations ([myricetin]/[Lys]o2.2) of myricetin, which is in accordance with the quenching mechanism of HSA or BSA by myricetin studied in the previous literature [16,17].…”
Section: Quenching Mechanism Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…3 (Table 1) are 3 orders of magnitude greater than the maximum diffusion collision quenching rate constant (2.0 Â 10 10 L mol À 1 s À 1 ) of a variety of quenchers with biopolymer [15]. Therefore, the fluorescence quenching of Lys by myricetin with or without Cu 2 + or Fe 3 + should be resulting from static quenching mechanism owing to a complex formation rather than a dynamic quenching mechanism at low concentrations ([myricetin]/[Lys]o2.2) of myricetin, which is in accordance with the quenching mechanism of HSA or BSA by myricetin studied in the previous literature [16,17].…”
Section: Quenching Mechanism Analysissupporting
confidence: 71%
“…Therefore, the reduction of K and n may result from the competition of metal ions and myricetin at higher concentrations of myricetin. However, it also can be observed that the binding constant of myricetin-Lys complex is a little larger than that of myricetin-HSA complex or myricetin-BSA complex [16,17]. This result may arise from the stronger hydrophobic forces between the aromatic ring of myricetin and the hydrophobic amino acid residues of Lys.…”
Section: Influences Of Common Ions On Binding Constantmentioning
confidence: 71%
“…30,31 EGCg substantially diminished the fluorescence lifetime of Trp 213 in a pH-dependent fashion, reducing the lifetime by about 50% at pH 5.0 or 7.4 (Table 2). At the same pH values, EGCg diminished the fluorescence lifetime of Trp 134 about 15–25% (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…The instrumental response function was recorded sequentially using a scattering solution and a time calibration of 114 ps/channel. Data were analysed using a sum of exponentials, employing a non‐linear least squares reconvolution analysis from Horiba (Jobin Yvon, IBH Ltd), of the form : f()t=truetrue∑i=1naiexp()tτi where τ i are the decay times, a i is the amplitude of the components at t = 0 and n is the number of decay times.…”
Section: Methodsmentioning
confidence: 99%